TRα1 mutant suppresses KLF9 to cause endometrial metaplasia with ectopic IL-33 expression leading to uterine fibrosis and infertility - Elijah Edmondson; Takahito Kimura; Eunmi Hwang; Minjun Kim; Andrew Warner; Yuelin Zhu; Li Zhao; Yanlin Yu; Xuguang Zhu; Maria Hernandez; Noemi Kedei; Sheue-yann Cheng (Scientific Reports)
Abstract Thyroid hormone receptors (TRs) mediate the genomic actions of thyroid hormone. Mutations of THRA gene cause a human disease known as resistance to thyroid hormone (RTHα). We created a mouse model expressing a dominant negative mutated TRα1 (Thra1PV/+ mice) that exhibits growth retardation, bone abnormalities, constipation, and anemia, as found in RTHα patients. In addition, female Thra1PV/+ mice exhibit decreased fertility. In the present study, we aimed to characterize the molecular events leading to infertility. Histologically, there was progressive uterine atrophy in Thra1PV/+ mutant mice, characterized by squamous metaplasia of the endometrial mucosa and endometrial fibrosis. RNA-seq analysis of laser-captured micro-dissected endometrium and spatial transcriptomics revealed a key role for Krüppel-like factor (Klf9), a directly-regulated TR target gene, in normal endometrial differentiation. Klf9 was suppressed in the endometrium of mice harboring mutated TRα1 and pathway analysis revealed that deficient Klf9 signaling was associated with squamous differentiation, consistent with the endometrial metaplasia observed histologically. Further, we showed that this metaplastic endometrial mucosa was the source of ectopic IL-33, which was associated with increased T-cell infiltrates, destruction of glands, and endometrial fibrosis. Our studies provide new insights to understand uterine epithelial morphogenesis and how thyroid dysfunction could lead to female infertility.